Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Evaluating $\int \frac{\sqrt{1+x^2}}{x^3} dx$. Any suggestions? I thought the replacement $t=\sinh x$ but in this way should solve the integral of $\frac{\cosh^2 t}{\sinh^3 t}$ (more difficult for me).

share|improve this question
    
$\def\csch{\mathop{\mathrm{csch}}}\cosh^2 t / \sinh^3 t = \coth^2 t \csch t = \csch t + \csch^3 t$ –  Hurkyl Jun 25 '12 at 0:13
add comment

4 Answers

up vote 2 down vote accepted

If you look at the form of the integrand, you can see it is

$$ \sqrt{1+x^2} $$

Which is similar to our pythagorean identity

$$ \sin^2(x) + \cos^2(x) = 1 $$

If you fiddle around with the equation, you can obtain

$$ \tan^2(x) + 1 = \sec^2(x) $$

$$\tan^2(x) + 1$$

looks just like

$$\sqrt{1+x^2}$$

So, we can make the substitution

$$ x = \tan(u)$$

$$\sqrt{1 + x^2} = \sqrt{1 + \tan^2(x)} = \sqrt{\sec^2(x)} = \sec(x) $$

Substituting in for your original problem, we get

$$ \int \frac{\sec(x)}{\tan^3(x)}\, dx $$

From here, I would simplify by writing in terms of sine and cosine and then solve. Remember that once you arrive at your answer, it will be in terms of u, in this case. You must draw a triangle with angle u, and since you have x = tan(u), you must derive from your triangle and substitute everything back in terms of x, your original variable.

share|improve this answer
add comment

Rewrite the integrand as follows: $$I=\int \frac{\sqrt{1+x^2}}{x^3}dx=\int\left(\sqrt{1+\frac{1}{x^2}}\right)\frac{dx}{x^2}=-\int\left(\sqrt{1+\frac{1}{x^2}}\right)d\left(\frac{1}{x}\right)$$ Now let $t=\frac{1}{x}$ $$I=-\int\sqrt{1+t^2}dt$$ The latter is a table integral (or you can let $x=\sinh t$ now)

share|improve this answer
add comment

Put $t= \tan\theta$ , then what you get is $$\int \frac{\tan\theta}{\tan^{3}\theta} \cdot \frac{1}{\cos^{2}\theta} \ d\theta = \int \csc^{2}\theta \ d \theta$$

share|improve this answer
    
Just a nitpick, maybe you mean $x=\tan \theta$. Likewise $\sqrt{1+\tan^2 \theta}=\sec^2\theta\ne\tan\theta$ –  E.O. Jun 24 '12 at 13:19
add comment

Let I = ∫ √(1 - x^2) / x^3 dx

Put u = x^2, du = 2x dx

Then I = ∫ (√(1 - u) / (2x^4)) du

=∫ (√(1 -  u) / (2u^2)) du

Put u = 1 – v^2, v ≥ 0, so du = -2vdv

So I = ∫ v / (1 – v^2)^2 * (-2v) dv

Let -2 v^2 / (1 – v^2)^2 = a/(1-v) + b/(1-v)^2 + c/(1+v) + d/(1+v)^2

Then -2v^2 = a(1-v)(1+v)^2 + b(1+v)^2 + c(1- v)^2(1+ v) + d(1- v)^2

put v = 1: -2 = 4b

put v = -1: -2 = 4d

Compare coefficients of v^3: 0 = -a + c

Compare constant terms: 0 = a + b + c + d, = a + c – 1

So a = ½ = c = -b = -d

So I = ½ ∫ (1/(1-v) – 1/(1-v)^2 + 1/(1-v) + 1/(1-v)^2) dv

    =  ½ (ln (A * (1 + v) / (1 - v)) + 1/(1 - v) – 1/(1 + v) )

    =  ½ ln (A * (1 + v) / (1 - v)) + v/(1 – v^2)

    =  ½ ln (A * (1 + √(1 – x^2)) / (1 - √(1 – x^2)) ) + √(1 – x^2) / x^2
share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.